Posttraumatic pneumacephalus: etiopathogenesis, diagnostics, methods of surgical treatment. Clinical case - V. A. Byvaltsev (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Studying an opportunity to optimize the treatment of the patients with severe traumatic brain injuries is a topical issue in modern neurosurgery. Traumatic tension pneumocephalus is one of life-threatening conditions which accompanies severe TB1 and is often complicated with posttraumatic liquorrhea and mass effect. Materials and methods. We carried out systematic search in Russian and foreign medical databases (Medline, Russian Science Citation Index, EMedicine, UMKB) concerning our theme. We included the following words in our search request: tension pneumocephalus, mass effect, valve mechanism, treatment. The result of conducted review of literature was writing the clinic lecture, studying current status of the problem of etiopathogenesis, diagnostics and surveillance of the patients with tension pneumocephalus. The article presenas clinical case of successful surgical treatment of a patient with traumatic tension pneumocephalus. Conclusion. There are no uniform standards of urveillance of the patients with tension pneumocephalus. Based on our own experience, we determined that minimally invasive surgery is a method of choice among reconstructive craniofacial surgeries in the treatment of patients with traumatic tension pneumocephalus. It decreases the risks of intra- and postoperative complication. Compliance, using external ventricular drainage and repeated lumbar punctures with prevention of inflammatory complications helped stopping nasal liquorrhea and eliminating mass effect which caused absolute regression of neurological signs.